XUV Emission from Autoionizing Hole States Induced by Intense XUV-FEL at Intensities up to 10(17) W/cm(2) - Rosmej, F; Galtier, E; Riley, D; Dzelzainis, T; Heinmann, P; Khattak, F; Lee, R; Nagler, B; Nelson, A; Tschentscher, T; Vinko, S; Whitcher, T; et al. (2010)
Aluminium targets were irradiated with 92 eV radiation from FLASH Free Electron Laser at DESY at intensities up to 1017 W/cm2 by focussing the beam on target down to a spot size of ∼1 μm by means of a parabolic mirror. High resolution XUV spectroscopy was used to identify aluminium emission from complex hole-states. Simulations carried out with the MARIA code show that the emission characterizes the electron heating in the transition phase solid-atomic. The analysis allows constructing a simple model of electron heating via Auger electrons. © 2010 IOP Publishing Ltd.